Foundation of operating practices of seed meal moisture and heat treatment on oil extraction from castor beans - Didur, Volodymyr; Дідур, Володимир Аксентійович; Дидур, Владимир Аксентиевич; Chebanov, Andrey; Aseev, Anatolii (Tavria state agrotechnological university, 2017)
Moisture and heat treatment of the castor beans with intensive mixing and bringing its humidity and temperature to optimum values for a given period of time causes a change in a number of physical and chemical properties of the castor-oil seed meal and oil contained in it. This promotes a better oil extraction effect. Moist and heat treatment is one of the most important technological operations in the castor bean preparation for the oil extraction through pressing and has a decisive influence on the quantity and quality of the final products: oil, oilcake or solvent cake. To substantiate the necessary operating practices for moisture and heat treatment of the castor-oil seed meal, an experimental complex was developed to extract oil from oil-bearing raw materials and the experiment procedure was determined. Experimental researches have established several operating practices of castor-oil seed meal roasting. 1) At steam pressure in a steam generator of 3 kg / cm2, the seed meal moistening time (at an initial humidity of 5.8%) to a moisture content of 10 ... 13.5% is 30 ... 55 seconds, and the drying time to a humidity of 6 ... 9% is 75 ... 150 minutes; 2) at a steam pressure of 4 kg / cm2, the seed meal moistening time (at an initial humidity of 5.8%) to a moisture content of 10 ... 13.5% is 35 ... 60 seconds, and the drying time to a humidity of 6 ... 9% is 75 ... 150 minutes; 3) at a steam pressure of 5 kg / cm2, the seed meal moistening time (at an initial humidity of 5.8%) to a humidity of 10 ... 13.5% is 45 ... 80 seconds, and the drying time to a humidity of 6 ... 9% is 55 ... 100 minutes. As a result of experimental studies, calibration curves have been obtained, which determine the time for the technological operations of seed meal moisture-heat treatment to obtain a target value of its moisture content.
Keywords: castor beans; ground seeds; seed meal; roasting; steam generator; steam pressure; moistening period; drying period; seed meal moisture; seed meal bed height